Isolation of curcumin from Curcuma longa Linne (Fam. Zingiberaceae) - Sayson, Fely Rose A.
Curcumin, the coloring matter of Curcuma longa Linne (Fam. Zingiberaceae), is extracted from the powdered airdried roots and rhizomes.